Real-time Interpretation of EEG Signals for Consciousness State Assessment - GONG, Jingming; Sui, Linfeng; Zhang, Ran; Li, Boning; Shen, Chengyuan; Cao, Jianting (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2023)
Assessing the level of consciousness is critical in clinical practice, especially for patients with traumatic brain injuries or those in a coma or vegetative state. Traditional methods like the Glasgow Coma Scale have limitations, such as inter-observer variability and low sensitivity. In recent years, electroencephalography (EEG) has emerged as a promising approach for assessing consciousness, offering non-invasive, real-time monitoring of brain activity. In this study, we propose a real-time analysis system for assessing consciousness levels using a portable EEG device. Our system analyzes EEG signals and provides valuable insights into consciousness levels, enabling prompt clinical interventions. The real-time nature of our system allows for continuous monitoring and immediate assessment of consciousness levels. Compared to traditional methods, our system offers advantages in terms of real-time functionality, providing a comprehensive evaluation of consciousness. Through extensive experiments using real patient data, our system demonstrates its value as a valuable tool for assessing consciousness levels in clinical practice. It offers healthcare professionals an efficient and reliable method for evaluating consciousness.